Reconstruction of functional human lips utilizing a prelaminated flap - Feinberg, Stephen E.; Marcelo, Cynthia L. (Frontiers in Bioengineering and Biotechnology, 2024)
Lips form a structure that are difficult to reconstruct after a traumatic avulsion injury or cancer ablative surgery secondary to loss of volumetric muscle mass. Traditional tissue engineering approaches of in vitro fabrication of mature tissue constructs can supply an alternative to the current surgical standard of care for functional lip reconstruction. We demonstrate a hybrid approach that combines the advantages of in situ muscle flap prefabrication with in vitro fabrication of an autogenous mucocutaneous construct as the laminate for prelamination to form a designer microvascular muscle free flap for lip reconstruction.